Ecology and biodiversity - "Balakrishan,A." (Jaipur, 2007)
The concept of biodiversity should be an expression of life which includes variability of al life forms and their organisation and inter-relationships from the molecular to the biosphere level, which includes cultural diversity. Biodiversity includes all forms of life and all areas that are home to natural and domesticated life forms. The threats to biodiversity are threats to all components of it; hence fragmented treatment of biodiversity must be rejected. Biodiversity is a concept which occuers at the balance between the spiritual understanding that, life is one and the scientific under standing that the diversity of life is inter connected.
Keywords: Ecology